Critical Literacy for ELT in Indonesia: What EFL Teachers should be Aware of - Anitha Thalib Mbau; Bambang Sugeng (Journal of English Language Teaching and Linguistics, 2019)
This article explores the basic and important issues related to critical literacy for ELT in Indonesia. Hopefully, it could contribute to improving EFL teachers’ understanding of critical literacy, particularly in Indonesia. Critical literacy is still considered as a new approach in EFL contexts. However, it is promising such benefits for both students and teachers for it might contribute to developing both teachers’ and students’ critical manners in reading and writing. This article describes the concept of critical literacy. Then, it elaborates the appropriate learning sources and activities to support the development of students’ critical literacy. After that, it describes some challenges for implementing critical literacy in ELT in the Indonesian context briefly. Finally, it offers conclusions on the important points of the topic.